Direct Repeat Sequences are Implicated in the Regulation of Two Streptomyces Chitinase Promoters that are Subject to Carbon Catabolite Control - Delic, Ina; Robbins, Phillips; Westpheling, Janet (Proceedings of the National Academy of Sciences - PNAS, 1992)
We report the identification and partial characterization of the promoters for two chitinase genes from Streptomyces plicatus. Chitinases are a family of enzymes made by Streptomyces and other soil microbes to digest chitin, an abundant source of carbon and nitrogen in the soil. The promoter regions of two chitinases were defined by using transcriptional fusions to the xylE reporter gene. Transcription was shown to be glucose-sensitive and chitin-dependent. Each promoter contains a putative RNA polymerase binding site with a recognition sequence very similar to that observed in many eubacterial vegetatively expressed genes. In both promoters, a pair of 12-base-pair direct repeat sequences overlap the putative RNA polymerase binding sites. Further analysis of one of the promoters revealed that a single-base change within the direct repeat sequences resulted in glucose-resistant, chitin-independent expression in vivo. In addition, the promoter region that includes the direct repeat sequences was shown to interact with a sequence-specific DNA binding factor in vitro. Similar direct repeat sequences are present in other chitinase genes recently characterized, and we suggest that these repeats may be involved in repression and induction for this entire class of catabolite-controlled genes.